Concern between medication non-adherence and diabetes associated depression - Chary, Krishnan Vengadaragava; Swaminathan, Porchelvan (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Diabetes mellitus is one of the health disorders that acquire mankind immensely. An ominous twin of diabetes mellitus is diabetes associated depression which is often unrecognised in routine diabetic care. The objective of this study was to find the prevalence and correlation between medication adherence and diabetes associated depression. Methods: It is a conducted as cross sectional study using Morisky medication adherence scale to evaluate treatment adherence of type II diabetes mellitus. Patient health questionnaire-9 was used to scale the level of depression among our study subjects. Correlation between measures of treatment non adherence and level of depression was elucidated. Results: Out of 250 patients, 167 (66.8%) (Males -103, Females-64) and 83 (33.2%) (Males-31, Females-52) subjects has medium & low adherence to medication with an average score 6.8 and 4.2 respectively. Total prevalence of depression among diabetics in our study is 41.1% (males-19.2%, females 21.9%). Percentage of patients found to have minor depression was 22.3 % and 18.8 % of depressive subjects falls under major depression category according to PHQ-9 questionnaire with average score of 8.6 for minor depression and 11.9 for major depression. Positive correlation is seen between medication non adherence and diabetes associated depression (Low adherence & Major depression -0.85, Medium adherence &Minor depression -0.79). Conclusions: Unnoticed depression among diabetic individuals reduces treatment adherence and must be addressed in any patient showing poor response to the treatment. Improving treatment adherence helps to combat diabetes as well as depression.